ANALISIS KEPADATAN PENDUDUK TERHADAP TINGKAT PENGANGGURAN SEBELUM DAN DI SAAT (COVID-19) DI KOTA PADANG - Nina Ismayani (Universitas Tamansiswa Padang, 2022)
This study aims to analyze population density and its effect on the unemployment rate that occurred in the city of Padang (before and during Covid-19) as well as the policies taken to overcome the existing unemployment rate. The sample of this research is the people who are the labor force in the city of Padang. Management of research data is carried out using Arcgis or GIS software which produces maps of population density levels and Simple Linear Regression using SPSS Software. This type of research used is quantitative descriptive research. Base on result, it shows that the population density in the city of Padang has increased by 242 people/km2 in 2020 by having as many as four (4) density classification classes consisting of class I (low density), class II (medium density), class III (slightlyhighdensity) and classification IV (highdensity). The largest population concentration in the districts of East Padang, North Padang and Nanggalo. In addition, the effect of population density on the unemployment rate in Padang City is 62% in 2019 and 69% in 2020. Thus, it can be concluded that in 2020 the unemployment rate has increased by 7%, this is due to population density, which continues to increase and is added by the Covid-19 pandemic which affects the depletion of community jobs.